HUMAN RIGHTS PROOFING DIGITAL SURVEILLANCE TECHNOLOGIES: THE REFLEXIVE DST WUNDERKAMMER FOR CIVIL SOCIETY ORGANISATIONS - Farries, Elizabeth Erin (Trinity College Dublin. School of Law. Discipline of Law, 2023)
I have explored in this thesis how Digital Surveillance Tech (DST) can be human rights proofed in areas of privacy to help emancipate vulnerabilised communities. Human rights proofing refers to creating forms of human rights protection and vetting the human rights impact of a particular DST against intersecting oppressions with a flexible future orientation for rapidly changing DST. I conceptualise the DST Wunderkammer as the model for variegated assemblages of Civil Society Organisation (CSO) actors, legal and regulatory artefacts, and human rights proofing actions around DST. I develop a self-reflexive methodology for CSO actors to observe, assess, and direct the DST Wunderkammer.
APPROVED
Keywords: DST Wunderkammer; Human Rights Proof; human rights; privacy; Civil Society Organisations; participatory action-research; self-reflexive analysis; digital surveillance technology